Silica composite material with efficient thermal protection and wave-transparent properties for radome

Through the method of combining the needle puncture process with the sol-gel method, SiO2/SiO2 needle puncture fabric composite material was prepared, which solved the problems of degradation in performance and poor wave transmittance at high temperatures, achieved the improvement of efficient thermal protection and wave transmittance, and reduced the preparation cost.

CN119591392APending Publication Date: 2025-03-11JIANGNAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411635679.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing radome materials have deteriorated performance in high temperature environments, poor wave transmittance, and complex preparation process and high cost, which limit their application.

Method used

The SiO2/SiO2 needle-punched fabric composite was prepared by the sol-gel method. By alternately laying silica satin cloth and mesh, and nitric acid treatment and densification, a radome material with high efficiency thermal protection and wave transmissive properties was prepared.

Benefits of technology

The performance stability and wave transmittance of the material at high temperatures are achieved, the cost and preparation difficulty of the material are reduced, and high-reliability, multifunctional, and high-load high-temperature wave transmittance materials are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591392A_ABST
    Figure CN119591392A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon dioxide composite material with efficient thermal protection and wave-transparent performance for an antenna housing, and belongs to the technical field of high-temperature antenna housings and structural wave-transparent composite materials. The prefabricated body is prepared by a needling lamination process, and the defect that the interlayer mechanical property effect of a 2D fabric structure is not ideal is overcome. The efficient thermal protection and wave-transparent silicon dioxide composite material prepared by the preparation method disclosed by the invention is relatively excellent in comprehensive performance, relatively low in dielectric loss angle tangent value and dielectric constant and excellent in mechanical property, and is a novel multifunctional material. The method plays an important role in radio systems of aerospace crafts such as radomes, carrier rockets, airships, missiles and return satellites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon dioxide composite material for a radome having both high-efficiency thermal protection and wave-transmitting properties, and belongs to the technical field of high-temperature radomes and structural wave-transmitting composite materials. Background Art

[0002] Radomes are key components in spacecraft, aircraft, and radar equipment. They are used to protect antennas from environmental factors and are required to have good wave transmission performance. Existing radome materials and preparation processes have been widely used in the production of various types of radomes, but they still face many problems in actual use.

[0003] Poor high temperature performance. Many radome materials are prone to deformation, cracking, or even burning in high temperature environments, resulting in a decrease in the mechanical properties and wave transmission performance of the materials. In particular, in the high temperature and high speed environment of the aerospace field, insufficient heat resistance becomes a limiting factor. Although PTFE-based composite materials and phenolic resin-based composite materials have improved heat resistance to a certain extent, they still cannot meet the use requirements under extreme conditions.

[0004] Poor wave transmittance: The wave transmittance of the radome is closely related to the dielectric constant of the material. Existing glass fiber and epoxy resin-based composite materials have low wave transmittance in specific frequency bands, which affects the signal transmission quality. Although quartz fiber and PTFE-based materials have good wave transmittance, the cost of quartz fiber materials is high and the processability of PTFE materials is poor, which increases the difficulty of preparation.

[0005] SiO 2 / SiO 2 Ceramic-based composite materials have excellent thermal, mechanical and dielectric comprehensive properties and are widely used in the field of high-temperature wave-transmitting materials. Patent CN110272269A discloses the use of quartz fiber to prepare a ceramic-based composite antenna cover; Patent CN110342913A discloses the use of quartz fiber cloth to prepare a ceramic-based A-type sandwich wave-transmitting antenna cover; Patent CN106007760B discloses the use of quartz fiber bundles as reinforcements, and composites a silicon dioxide matrix layer and a silicon nitride matrix on the surface to improve the ablation resistance and high temperature resistance of the composite ceramic antenna cover without affecting the electrical properties of the material.

[0006] For patent CN110272269A, there may be some technical difficulties in its preparation process, such as uniformity and density control problems. And the material properties may be affected by the preparation conditions (such as temperature, pressure, etc.), resulting in performance fluctuations. For patent CN110342913A, potential defects may include: the interfacial bonding problems that may exist in the sandwich structure affect the stability and wave transmission performance of the overall structure. The stability and durability of material performance under high temperature environment may require further research. For patent CN106007760B: there may be problems with the interface bonding between the reinforcement and the matrix, affecting the overall performance of the material. The preparation cost of the material may be high, limiting its large-scale application. The long-term performance and reliability of the material in extreme environments need to be further verified, especially under high temperature conditions.

[0007] Therefore, there is an urgent need to develop a radome material that is resistant to high temperatures and has excellent wave-transmitting properties, which has extremely high practical and economic value. Summary of the invention

[0008] [Technical issues]

[0009] Traditional 3D and 2.5D weaving are limited in mass application due to their complex process and high cost, while the mechanical properties between layers of 2D fabric structures are not ideal. The radome has very strict requirements on the comprehensive performance of materials, covering mechanical, thermal, electrical, magnetic, chemical and other aspects. Although a single ceramic may be outstanding in some aspects, its mechanical properties are poor, it is not resistant to rain erosion, and it is difficult to form large-scale components. However, they all have certain shortcomings that restrict their application. So far, there is no material with excellent performance in all aspects.

[0010] Quartz ceramics have excellent high-temperature dielectric properties and thermophysical properties, but poor mechanical properties and low resistance to rain erosion, which limits their wave transmission performance and restricts their application in high Mach (≥5Ma) fields.

[0011] [Technical solution]

[0012] In order to solve the above problems, the present invention uses a needle punching process, a silica satin cloth, and a mesh tire to prepare a preform, and then uses a sol-gel method to prepare SiO 2 / SiO 2 Needle-punched fabric composite material. Its wave transmission performance and load-bearing performance at room temperature and high temperature were tested.

[0013] The needle punching preform process of the present invention overcomes the disadvantage of weak interlayer strength of 2D layered preforms, and at the same time overcomes the disadvantages of complex process, high cost and long cycle of 3D woven preforms. However, the mechanical properties of traditional staple needle punching are poor and cannot meet the use requirements of high-temperature antenna covers.

[0014] The present invention combines the needle punching process with the two-dimensional fabric to obtain SiO 2 / SiO 2 Needle-punched composite materials not only have good load-bearing and wave-transmitting properties, but also have design flexibility. By designing the arrangement between different layers, excellent wave-transmitting design can be achieved, providing an effective way for high-reliability, multi-functional, high-load-bearing and high-temperature wave-transmitting materials.

[0015] The first object of the present invention is to provide a method for preparing a silicon dioxide composite material for a radome, comprising the steps of:

[0016] (1) two layers of silica satin cloth and one layer of mesh are alternately laid and continuously needle-punched to prepare a preform;

[0017] (2) immersing the preform in a nitric acid solution, rinsing, and drying to obtain a preform treated with nitric acid;

[0018] (3) densifying the preform treated with nitric acid to obtain a silicon dioxide composite material;

[0019] (4) A raised cross pattern is etched on the surface of the silica composite material to obtain a silica composite material for a radome.

[0020] In one embodiment, the alternating layers in step (1) are two layers of silica satin cloth and one layer of mesh as one unit, and 6 to 8 units are laid.

[0021] In one embodiment, the number of puncture holes in the continuous acupuncture in step (1) is 80 to 110 per 25 cm 2 .

[0022] In one embodiment, the preparation method of the silica satin cloth in step (1) is:

[0023] Silica fibers with a fineness of 180-200 tex are carded and drawn to obtain fiber bundles, and the fiber bundles are twisted, plied and woven to obtain silica satin fabric; wherein the warp and weft density of the weaving is 70-90 strands / 10 cm.

[0024] In one embodiment, the satin cloth is an 8-piece 5-fly weft satin weave, that is, R=8, S=5; the specific method is: take the lower left corner of the large square Rj=Rw=R circled on the graph paper as the starting point, draw a graph according to the weft flying number, move one weft yarn (a row of horizontal grids) upward from the starting point, count Sw small grids to the right (or left), and get the second separate weave point, and so on, until a weave cycle is reached; the straight threading method is adopted when threading the reed, and 2 to 4 reeds are inserted into each reed tooth.

[0025] In one embodiment, the density of the silica satin cloth is 320 g / m 2, the dielectric constant of silica satin cloth is 3.74.

[0026] In one embodiment, the size of the preform is 260×260×7 (mm), the fiber volume fraction is 38.43%, and the density is 0.846 g / cm 3 , thickness is 7mm.

[0027] In one embodiment, the immersion in step (2) is performed at 75 to 85° C. in a nitric acid solution with a concentration of 20% to 35% w / v (g / mL) for 10 to 15 hours.

[0028] In one embodiment, the densification step in step (3) is:

[0029] The preform treated with nitric acid is mixed with silica sol and impregnated;

[0030] After impregnation, it is cured, dried and heat treated.

[0031] In one embodiment, the densification step in step (3) is:

[0032] The preform treated with nitric acid is placed in a pressure vessel, vacuumed to 3-5 KPa, and silica sol (high-purity silica sol in accordance with GJB2031-94 standard) is added, and after soaking for 3-5 hours, an external pressure of 0.3-0.8 MPa is applied and maintained for 1-5 hours (immersion);

[0033] Place the sample at 85-95°C for 20-30 hours (curing and drying);

[0034] The furnace chamber is filled with nitrogen atmosphere and heat treatment is carried out according to the heating system. The room temperature is heated to 95-105°C at 480-600°C / h for 1-3 hours; then the temperature is heated to 350-450°C at 140-160°C / h for 1-2 hours, and finally the temperature is heated to 800-900°C at a rate of 140-160°C / h for 2-6 hours and then naturally cooled (heat treatment process).

[0035] In one embodiment, the prepared SiO 2 / SiO 2 The thickness of the composite material is 3 to 5 mm.

[0036] In one embodiment, the drying in step (2) is performed at 100-120° C. for 18-24 hours.

[0037] In one embodiment, etching comprises the steps of:

[0038] The silica composite material is cleaned to remove dust and oil on the surface; the copper foil is bonded to the silica composite material; a layer of sensitive photoresist is evenly applied on the surface of the copper foil; a cross mold is placed on the copper foil coated with the photoresist and irradiated with ultraviolet light; the photoresist not irradiated by ultraviolet light is removed from the copper foil, leaving a cross pattern formed after irradiation with ultraviolet light; the copper foil is immersed in an etching solution to remove the copper part not protected by the photoresist, forming a cross pattern.

[0039] In one embodiment, the width of the cross pattern in step (4) is 8 to 12 mm, and the thickness of the pattern is 0.4 to 0.8 mm; preferably, the thickness of the pattern is 0.4 to 0.6 mm.

[0040] In one embodiment, the cross pattern is a cross pattern with equal length and width.

[0041] In one embodiment, the normal temperature in the present invention is 15-25°C.

[0042] The second object of the present invention is to provide a silica composite material for a radome prepared by any of the above methods.

[0043] The third object of the present invention is to provide a highly efficient thermal protection and wave-transmitting radome, wherein the radome is prepared from the above-mentioned silica composite material for radome.

[0044] A fourth object of the present invention is to provide application of the above-mentioned silica composite material for radome in the fields of aerospace and electronic communications.

[0045] In one embodiment, the application of the silica composite material for radome in the radio systems of spacecraft such as radomes, launch vehicles, spacecraft, missiles and recoverable satellites will play an important role.

[0046] A fifth object of the present invention is to provide a method for simultaneously improving the bearing performance, thermal protection performance and wave transmission performance of a radome, by using a silica composite material for a radome to prepare a radome;

[0047] The preparation method of the silicon dioxide composite material for the radome comprises:

[0048] (1) two layers of silica satin cloth and one layer of mesh are alternately laid and continuously needle-punched to prepare a preform;

[0049] (2) immersing the preform in a nitric acid solution, rinsing, and drying to obtain a preform treated with nitric acid;

[0050] (3) densifying the preform treated with nitric acid to obtain a silicon dioxide composite material;

[0051] (4) A raised cross pattern is etched on the surface of the silica composite material to obtain a silica composite material for a radome.

[0052] In one embodiment, the alternating layers in step (1) are two layers of silica satin fabric and one layer of mesh as a unit, and 6 to 8 units are laid;

[0053] The preparation method of the silica satin cloth in step (1) is:

[0054] Silica fibers with a fineness of 180 to 200 tex are combed and drawn to obtain fiber bundles, and the fiber bundles are twisted, plied, and woven to obtain silica satin fabric; wherein the warp and weft density of the weaving is 80 strands / 10 cm;

[0055] In step (2), the immersion is performed in a nitric acid solution (the solvent is water) with a concentration of 20% to 35% w / v (g / mL) at 75 to 85° C. for 10 to 15 hours;

[0056] In step (4), the width of the cross pattern is 8 to 12 mm, and the thickness is 0.4 to 0.8 mm; preferably, the thickness is 0.4 to 0.6 mm.

[0057] [Beneficial Effects]

[0058] (1) Compared with traditional wave-transmitting materials, the high-efficiency thermal protection and wave-transmitting silica composite material of the present invention still has good performance stability in harsh environments and is not easy to delaminate and fall off.

[0059] (2) Compared with other materials, the high-efficiency thermal protection and wave-transmitting silica composite material of the present invention has better impedance matching performance, and can allow more electromagnetic waves to effectively enter and pass through the material at high temperatures (wave transmittance reaches more than 90%; dielectric constant is less than 3.1 at 500°C; dielectric constant is less than 3.6 at 1000°C).

[0060] (3) Compared with pure quartz ceramic materials, the high-efficiency thermal protection and wave-transmitting silica composite material of the present invention improves its problems of low mechanical strength, poor bearing capacity and poor machinability, and effectively improves its wave transmission and bearing performance (tensile strength reaches above 38.9 MPa, bending strength reaches above 91.2 MPa, and shear strength reaches above 12.3 MPa).

[0061] (4) The present invention uses a needle punching lamination process to prepare the preform, which improves the disadvantage of unsatisfactory mechanical properties between layers of the 2D fabric structure. The composite material is prepared by the sol-gel method, and its sintering temperature is low, generally below 1000°C, and the damage to the fiber is small.

[0062] (5) The high-efficiency thermal protection and wave-transmitting silica composite material of the present invention has excellent comprehensive performance, has a low dielectric loss tangent value and dielectric constant and excellent mechanical properties, and is a new type of multifunctional material. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 This is the organization diagram of the silica satin cloth in Example 1;

[0064] Figure 2 Schematic diagram of the structure of the silica preform in Example 1, wherein 1 is a satin cloth, 2 is a mesh, and 3 is a needle;

[0065] Figure 3 Schematic diagram of the needle-punched silica composite material in Example 1, wherein 1 is a layer of satin cloth, and 2 is a mesh substrate;

[0066] Figure 4 is a cross-shaped protrusion structure after etching, where h is the thickness, and a and b are the widths;

[0067] Figure 5 It is a block-shaped raised structure after etching. DETAILED DESCRIPTION

[0068] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0069] Test method:

[0070] 1. Tensile performance test:

[0071] The tensile properties of the composite material were tested on an Instron 8801 electronic universal testing machine, where the stress and strain of the material were measured by an Epsilon 3548 high temperature extensometer. The test standard was GJB6475-2008 "Test method for tensile properties of continuous fiber reinforced ceramic matrix composite materials at room temperature", and the average value of 5 specimens was taken for analysis.

[0072] 2. Bending performance test

[0073] The bending stress-strain curve of the needle-punched silica composite material was tested by the three-point bending method. During the test, the span was set to 30 mm, the loading rate was 0.5 mm / min, and the sample size was 36×4×3 (mm). The average value of 5 specimens was taken for analysis.

[0074] 3. Interlaminar shear strength

[0075] The composite material was subjected to interlaminar shear test on MTS Criterion C44 electronic universal testing machine. The test standard was GB3357-82. The sample size was 25×5×3 (mm). The average value of 5 specimens was taken for analysis.

[0076] 4. Thermal conductivity test

[0077] The specific heat capacity of quartz ceramic composite materials was measured by the drop method. Referring to GJB330A-2000, the sample appearance size was Ф14mm×30mm, and the average value of 5 specimens was taken for analysis.

[0078] 5. Dielectric performance test

[0079] SiO 2 / SiO 2 The dielectric properties (dielectric constant ε and loss tangent tanδ) of the composite material were measured by the resonant cavity method. In the range of 8 to 12 GHz, the sample size was 22.86 mm × 10.16 mm × 3 mm, and in the range of 12 to 18 GHz, the sample size was 15.8 mm × 7.9 mm × 3 mm. The average value of 5 specimens was taken for analysis.

[0080] The raw materials used in the examples are:

[0081] Silica fiber: short fiber, fineness 195tex, purchased from Changsha Jingyou New Material Technology Co., Ltd.

[0082] Silica sol: High-purity silica sol, in line with GJB2031-94 standard, with a milky white colloid appearance, without gel, sediment and foreign impurities.

[0083] Nitric acid: concentration is 25% w / v (g / mL), analytical grade, light yellow liquid.

[0084] Net tire: Product model SJ117, density 85g / cm 2 , dielectric constant: 3.7, purchased from Henan Shenjiu Tianhang New Materials Co., Ltd.

[0085] Copper foil: product model tu2, purchased from Shenzhen Chengnuo New Materials Co., Ltd.

[0086] Carbon fiber: T300-3K carbon fiber (CF) was purchased from Toray Group.

[0087] Si 3 N 4 Fiber: purchased from Shandong Stari Metal Materials Co., Ltd.

[0088] Example 1

[0089] A method for preparing a high-efficiency thermal protection and wave-transmitting silica composite material for a radome, comprising the steps of:

[0090] (1) Preparation of needle-punched SiO 2 / SiO 2 Prefabs

[0091] Silica fiber with a fineness of 195 tex is combed and drawn to form a uniform fiber bundle, which is then twisted and ply-coated before being woven on a machine (satin fabric is an 8-piece 5-fly weft satin fabric with a structure such as Figure 1 As shown), a silica satin fabric is formed; wherein the warp and weft density is 80 strands / 10cm, and the density of the fabric is 320g / m 2 , the dielectric constant of the formed satin cloth is 3.74;

[0092] Two layers of silica satin cloth and one layer of mesh are used as a small unit. Seven small units are used for acupuncture, and the number of puncture needle holes is 100 / 25cm. 2 (Acupuncture density is 5×5 needles / cm 2 ), a preform is prepared, the structure is as follows Figure 2 As shown;

[0093] (2) Nitric acid treatment of preform

[0094] The preform was immersed in a hot nitric acid solution (80° C.) with a concentration of 25% w / v (g / mL) for 12 hours, and then repeatedly ultrasonically rinsed with deionized water, and then dried at 120° C. for 24 hours to obtain a preform treated with nitric acid;

[0095] (3) Densification treatment of silica composite materials

[0096] The preform treated with nitric acid is densified in the following steps:

[0097] The preform treated with nitric acid was placed in a pressure vessel, vacuumed to 4 kPa, silica sol was added, and after soaking for 4 hours, an external pressure of 0.5 MPa was applied and maintained for 2 hours (immersion);

[0098] Place the sample in a blast drying oven and heat it to 90°C for 24 hours (curing and drying);

[0099] The furnace chamber was filled with nitrogen atmosphere, and heat treatment was performed according to the heating system. The room temperature was heated to 100°C at 10°C / min for 2 hours; then the temperature was raised to 400°C at 150°C / h for 2 hours, and finally the temperature was raised to 850°C at a rate of 150°C / h for 4 hours and then naturally cooled (heat treatment process), and SiO with a thickness of 3 mm was prepared. 2 / SiO 2 Composite materials, structures such as Figure 3As shown;

[0100] (4) Etching process

[0101] Pretreatment: First, SiO 2 / SiO 2 The surface of the composite material is cleaned to remove dust and oil on the surface in preparation for subsequent bonding and etching processes.

[0102] Bonding copper foil: Use epoxy resin adhesive to bond 20μm thick copper foil to SiO 2 / SiO 2 On composite materials. Ensure that the copper foil is firmly bonded to the substrate without bubbles.

[0103] Coating photoresist: Apply a layer of sensitive photoresist evenly on the surface of the copper foil. This material will undergo a chemical reaction when exposed to ultraviolet light.

[0104] Photolithography: A cross mold (0.5 mm thick and 10 mm wide) is placed on a copper foil coated with photoresist and irradiated with ultraviolet light. The resist in the area exposed to ultraviolet light reacts and is easily removed in the subsequent steps, while the resist in the unexposed area remains unchanged.

[0105] Development: The photoresist that has not been exposed to ultraviolet light is removed from the copper foil, leaving behind the cross pattern formed after exposure to ultraviolet light.

[0106] Etching: Immerse the copper foil in an etching solution to remove the copper portion not protected by the photoresist, forming a cross pattern. Removing the photoresist: After etching is complete, remove the remaining photoresist to reveal the complete etched copper pattern.

[0107] Post-processing: including cleaning and drying, removing the residues that may be produced during the etching process to ensure that the surface of the composite material is clean. The final etching thickness is 0.5mm, the width a and width b are both 10mm, and the structure is as follows Figure 4 shown.

[0108] Among them, etching time is a direct factor controlling etching depth. The longer the etching time, the deeper the etching depth is usually. The etching depth can be managed by precisely controlling the etching time. The design of the mold will also affect the etching depth. Although the thickness of the mold cannot directly determine the etching depth, the design and placement of the mold can affect the distribution and contact time of the etching solution, thereby indirectly affecting the etching depth.

[0109] Example 2

[0110] On the basis of Example 1, the needle punching in step (1) was changed to five small units, and the other steps were kept consistent with Example 1 to obtain a silica composite material for a radome.

[0111] Comparative Example 1

[0112] Based on Example 1, the acupuncture density in step (1) was changed to 3×3 (needles / cm 2 ), and the remaining steps are consistent with those in Example 1 to obtain a composite material.

[0113] Comparative Example 2

[0114] Based on Example 1, the acupuncture density in step (1) was changed to 8×8 (needles / cm 2 ), and the remaining steps are consistent with those in Example 1 to obtain a composite material.

[0115] Comparative Example 3

[0116] On the basis of Example 1, the silica fiber in step (1) was replaced with carbon fiber, and the remaining steps were kept the same as Example 1 to obtain C / SiO 2 Composite materials.

[0117] Comparative Example 4

[0118] On the basis of Example 1, the silica fiber in step (1) was replaced with Si 3 N 4 The remaining steps were the same as in Example 1 to obtain Si 3 N 4 / SiO 2 Composite materials.

[0119] Comparative Example 5

[0120] On the basis of Example 1, the etching process of step (4) is omitted, and the remaining steps are consistent with Example 1 to obtain a composite material.

[0121] Comparative Example 6

[0122] On the basis of Example 1, the etching thickness in step (4) was changed to 0.2 mm, and the remaining steps were kept consistent with Example 1 to obtain a composite material.

[0123] Comparative Example 7

[0124] On the basis of Example 1, the etching thickness in step (4) was changed to 1 mm, and the remaining steps were kept consistent with Example 1 to obtain a composite material.

[0125] Comparative Example 8

[0126] On the basis of Example 1, the etching pattern in step (4) is changed to a grid-like type with a side length of 12.5 mm and a thickness of 0.5 mm, and the structure is as follows: Figure 5As shown, the remaining steps are consistent with those in Example 1 to obtain a composite material.

[0127] The composite materials obtained in Examples 1 to 2 and Comparative Examples 1 to 8 were subjected to performance tests at room temperature. The test results are shown in Table 1.

[0128] Table 1 Performance test results

[0129]

[0130]

[0131] The results show that the mechanical properties and wave transmission properties of the silica composite materials for antenna covers prepared in Examples 1 and 2 are excellent. In particular, the dielectric constant of the composite material in Example 1 reaches 2.9, the loss tangent value reaches 0.0079, the wave transmittance reaches 92%, and the specific heat capacity is relatively high, with good thermal stability.

[0132] The dielectric properties of the composite materials obtained in Examples 1 to 2 and Comparative Examples 1 to 8 were tested at 500° C. and 1000° C. The test results are shown in Table 2.

[0133] Table 2 Dielectric properties

[0134]

[0135] The results show that the dielectric constant of the silica composite material for antenna cover prepared in Examples 1 to 2 is relatively low at either 500°C or 1000°C, and a good impedance match is formed with the free air. Electromagnetic waves can enter the interior of the composite material in large quantities and reduce the loss inside the material, effectively improving the wave transmission performance of the composite material.

[0136] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a silicon dioxide composite material for a radome, characterized in that: Includes steps: (1) two layers of silica satin cloth and one layer of mesh are alternately laid and continuously needle-punched to prepare a preform; (2) immersing the preform in a nitric acid solution, rinsing, and drying to obtain a preform treated with nitric acid; (3) densifying the preform treated with nitric acid to obtain a silicon dioxide composite material; (4) A raised cross pattern is etched on the surface of the silica composite material to obtain a silica composite material for a radome.

2. The method according to claim 1, characterized in that In step (1), the alternating layers are formed by two layers of silica satin cloth and one layer of mesh as one unit, and 6 to 8 units are laid.

3. The method according to claim 1, characterized in that The number of puncture holes in the continuous acupuncture in step (1) is 80 to 110 / 25 cm 2 .

4. The method according to claim 1, characterized in that: In step (2), the immersion is carried out at 75 to 85° C. in a nitric acid solution with a concentration of 20% to 35% w / v for 10 to 15 hours.

5. The method according to claim 1, characterized in that The thickness of the silicon dioxide composite material in step (3) is 3 to 5 mm.

6. The method according to claim 1, characterized in that In step (4), the width of the cross pattern is 8 to 12 mm, and the thickness is 0.4 to 0.6 mm.

7. The silicon dioxide composite material for antenna cover prepared by the method according to any one of claims 1 to 6.

8. A radome with both high-efficiency thermal protection and wave-transmitting performance, characterized in that: The radome is prepared from the silicon dioxide composite material for radome according to claim 7.

9. Application of the silica composite material for radome according to claim 7 in the fields of aerospace and electronic communications.

10. A method for simultaneously improving the bearing performance, thermal protection performance and wave transmission performance of a radome, characterized in that: preparing a radome using a silica composite material for a radome; The preparation method of the silicon dioxide composite material for the radome comprises: (1) two layers of silica satin cloth and one layer of mesh are alternately laid and continuously needle-punched to prepare a preform; (2) dipping the preform in a nitric acid solution, rinsing, and drying to obtain a preform treated with nitric acid; (3) densifying the preform treated with nitric acid to obtain a silicon dioxide composite material; (4) A raised cross pattern is etched on the surface of the silica composite material to obtain a silica composite material for a radome.

Citation Information

Patent Citations

  • Dual-substrate composite ceramic radome housing and its preparation method

    CN106007760B

  • Root-reinforced ceramic matrix composite radome and preparation method thereof

    CN110272269A

  • Preparation method of ceramic based A-type interlayer wave transparent radome

    CN110342913A